De novo germline and postzygotic mutations in AKT3, PIK3R2 and PIK3CA cause a spectrum of related megalencephaly syndromes - Rivière, Jean-Baptiste; Mirzaa, Ghayda M; O'Roak, Brian J; Beddaoui, Margaret; Alcantara, Diana; Conway, Robert L; St-Onge, Judith; Schwartzentruber, Jeremy A; Gripp, Karen W; Nikkel, Sarah M; Worthylake, Thea; Sullivan, Christopher T; et al. (Nature genetics, 2012)
William Dobyns and colleagues report de novo germline and postzygotic mutations in AKT3 , PIK3R2 and PIK3CA in the sporadic overgrowth syndromes megalencephaly-polymicrogyria-polydactyly-hydrocephalus (MPPH) and megalencephaly-capillary malformation (MCAP). Megalencephaly-capillary malformation (MCAP) and megalencephaly-polymicrogyria-polydactyly-hydrocephalus (MPPH) syndromes are sporadic overgrowth disorders associated with markedly enlarged brain size and other recognizable features 1 , 2 , 3 , 4 , 5 . We performed exome sequencing in 3 families with MCAP or MPPH, and our initial observations were confirmed in exomes from 7 individuals with MCAP and 174 control individuals, as well as in 40 additional subjects with megalencephaly, using a combination of Sanger sequencing, restriction enzyme assays and targeted deep sequencing. We identified de novo germline or postzygotic mutations in three core components of the phosphatidylinositol 3-kinase (PI3K)-AKT pathway. These include 2 mutations in AKT3 , 1 recurrent mutation in PIK3R2 in 11 unrelated families with MPPH and 15 mostly postzygotic mutations in PIK3CA in 23 individuals with MCAP and 1 with MPPH. Our data highlight the central role of PI3K-AKT signaling in vascular, limb and brain development and emphasize the power of massively parallel sequencing in a challenging context of phenotypic and genetic heterogeneity combined with postzygotic mosaicism.